Sirtuin Type 1 Mediates the Antidepressant Effect of S-Ketamine in a Chronic Unpredictable Stress Model - Hou, Lanwei; Miao, Jingyu; Meng, Haiwei; Liu, Xiao; Wang, Di; Tan, Yawen; Li, Chuangang (Frontiers in Psychiatry, 2022)
Background Major depressive disorder (MDD) refers to a mental disease with complex pathogenesis and treatment mechanism. S-ketamine exhibited high effectiveness in treating MDD. However, the pharmacological activity of S-ketamine has not been reported yet. Materials and Methods In this study, depression-like characteristics were induced by chronic unpredictable stress (CUS). After S-ketamine (15 mg/kg) was intraperitoneally injected, the behaviors of mice were tested by conducting open-field test, elevated plus maze test, tail suspension test, and forced swimming test. Bilateral injection of sirtuin type 1 (SIRT1) inhibitor EX-527 was injected into the medial prefrontal cortex (mPFC) to upregulate the SIRT1 expression. The expression of SIRT1 and brain-derived neurotrophic factor (BDNF) was detected by conducting Western blot and immunofluorescence assays. Meanwhile, the synaptic ultrastructure was detected by transmission electron microscopy. Results In this study, the mice showed depression-like behavior in a series of behavioral tests. After the treatment with S-ketamine, the depression-like behavior stopped. Further, the synaptic ultrastructure in mPFC, including the decreased curvature of the post synaptic density and thinning of the postsynaptic density, improved after the S-ketamine treatment. Moreover, we found that S-ketamine had the possibility of spontaneous binding with SIRT1 at the molecular level and reversed CUS-induced SIRT1 reduction. Meanwhile, a positive relationship between SIRT1 and BDNF expression in mPFC and SIRT1 inhibitor limited the role of S-ketamine in reducing the depression-like behavior and increasing the BDNF level. Conclusion S-ketamine upregulated the SIRT1-mediated BDNF in mPFC and reversed the synaptic structural defects caused by CUS. SIRT1 is a mediator of S-ketamine in alleviating depression-like behavior.